Does it pay to be social responsible? Portuguese SMEs feedback - Fonseca, Luís (2016)
The research on corporate social responsibility has been focused mainly on Anglo-Saxon countries and big companies. Most scholars agree there is a positive relationship between companies social and economic performance, however, this is not unanimous. Moreover,during economic downturns, companies struggle for survival and might consider corporate social responsibility efforts should be postponed. This research investigates if there is a positive relationship between social performance and key business results using a large sample of small and medium Portuguese companies over an extended period of time. The research results support the existence of valid positive relationships between companies’ social performance and key business results, confirming it does pay to invest in corporate social responsibility even in less favorable economic scenarios and for small and medium companies across all business sectors.